ANALISIS EFISIENSI TEKNIS KARET PERKEBUNAN RAKYAT KABUPATEN BANYUASIN PROVINSI SUMATERA SELATAN - Pratama, Ario; Syahni, Rahmat; Mahdi, Mahdi (Jurnal Social Economic of Agriculture, 2020)
The average productivity of rubber smallholder in Banyuasin Regency is 0,89 ton/ha lower than its potential productivity 1,5 ton/ha. This study aims to analyze the factors affecting rubber productivity, the level of technical efficiency and factors affecting technical inefficiency in rubber plantation at several group of plant age. The research used purposive sampling which obtained 60 samples of farmers as respondent and was conducted in Banyuasin Regency, South Sumatera Province from April to June 2020. Data were analyzed using stochastic frontier Cobb Douglas analysis. The results showed that factors affecting rubber productivity were TSP, Fungicide, Herbicide, labour, numbers of plant (tree), plant age and clone. The level of rubber smallholder technical efficiency showed the various amount from 0.50 to 0.97 with average level 0.87. The highest average level of rubber smallholder technical efficiency was found at group of plant age 6-15 with TE 0.91. Factors affecting technical inefficiency were farmerâ€™s education, training and farmers status.Â Keywords: Productivity, technical efficiency, rubber, stochastic frontierÂ